ANALYSIS OF OCCUPATIONAL MORBIDITY OF WORKERS IN FOUNDRY - A. M. Lazarenkov; S. A. Horeva; V. V. Melnichenko (Литьë и металлургия, 2011)
The distribution of founders in whole on the foundry and on the casthouses of steel and iron casting as well is given on the basis of analysis of their occupational morbidity. Distribution of diseases by professions of workers is examined. the dependences of cases of occupational morbidity for 10 years period are given.